Using a Target Product Profile (TPP) to guide innovation for future In Vitro Diagnostic (IVD) developments in the United States - Ricky Soong; Elaine Bradford; Kenneth B. Yeh; Gene Olinger (Taylor & Francis Group, 2023)
ABSTRACTA well-developed Target Product Profile (TPP) is central to successful in vitro diagnostic (IVD) device developments. A TPP is a key document that outlines the desired attributes of a target product that is aimed at a particular disease. The TPP framework can highlight technological gaps and focus developments on meeting specific needs that advance the field. A survey of various diagnostic technologies, such as those employed for respiratory disease diagnosis, reveals significant innovations that have been accomplished during the COVID-19 public health emergency. Nevertheless, the entire IVD diagnostic landscape continues to evolve, and it is important for device developers to identify the challenges and set appropriate targets to avoid pitfalls. While a TPP does not necessarily guarantee market success of an IVD, it is an important tool that can help developers define appropriate criteria for their device. A TPP can guide them through the multi-faceted development process to meet consumer demands, while ensuring clinical utility, safety, and effectiveness of their products. The following discussion highlights the TPP process for IVD device developments through the application of the basic tenets in various case studies. The aim is to help developers traverse the proverbial 'valley of death', where many great concepts fail to reach market success, and to encourage positive developments in the field beyond current IVD device limitations.